PENGARUH PERLAKUAN BERBAGAI VARIETAS DAN KONSENTRASI NUTRISI AB MIX PADA HIDROPONIK SISTEM WICK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Arsela, Primadiyanti (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2018)
The study aims to determine the effect of various Tomato varieties and concentrations of AB Mix nutrition and the interaction on its growth and yield. The research used two factorial Randomized Block Design (RAK), the first factor was Tomato varieties with three levels which are v1 = Gem F1, v2 = Tymoti, v3 = Lentana. And the second factor is the AB Mix Concentration consists of three levels n1 = 2.5 ml L-1, n2 = 5 ml L-1 , n3 = 7.5 ml L-1 . The result of the first factor are various varieties have a very significant effect on parameters plant height, fruit weight and number of harvested fruit. The result of the second factor are AB Mix concentration have a significant effect on the height parameter and fruit weight. And the result in interaction treatment showed that treatment v2n1 has the heaviest of harvested fruit than others. Keywords: Tomato variety, AB Mix nutrition, Wick hydroponic